ESG Disclosure: Moderating Thin Capitalization, Transfer Pricing and Tax Aggressiveness - Reka Mayangsari, Sinta; Khoiru Rusydi, Mohamad; Amirya, Mirna (Universitas Muhammadiyah Malang, 2024)
Purpose: Empirically, this study aims to examine the role of ESG Disclosure in moderating thin capitalization and transfer pricing on tax aggressiveness. Methodology/approach: The population in this study is energy companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. By referring to associative research as the type of research and purposive sampling technique in determining the sample, 105 energy companies listed on the IDX from 2018-2022 were obtained. Multiple linear regression using MRA was used as the analysis technique with SPSS 29 as the analysis tool. Findings: The results showed that thin capitalization has a negative effect on tax aggressiveness and transfer pricing variables have a positive effect on tax aggressiveness. ESG disclosure in this study is able to weaken the relationship between thin capitalization and transfer pricing on tax aggressiveness. Practical implications: The implication of this study is that companies can better improve their tax planning through a deeper understanding of ESG disclosure, thin capitalization, transfer pricing, and tax aggressiveness. By paying attention to ESG factors, companies can not only optimize financial returns but also improve compliance and transparency, and minimize negative impacts on the environment and society. This research also provides valuable insights for investors, allowing them to evaluate the risks and opportunities associated with corporate tax planning, so that investment decisions can be more focused on sustainability and social responsibility. Originality/value: This study examines the tax aggressiveness strategy carried out by energy companies through thin capitalization and transfer pricing practices. The addition of ESG disclosure as a moderator in this study serves to narrow the use of tax regulation loopholes so as to weaken the practice.